1997
DOI: 10.1103/physrevc.56.2626
|View full text |Cite
|
Sign up to set email alerts
|

Quantum statistical correlations and single-particle distributions for slowly expanding systems with temperature profile

Abstract: Competition among particle evaporation, temperature gradient and flow is investigated in a phenomenological manner, based on a simultaneous analysis of quantum statistical correlations and momentum distributions for a non-relativistic, spherically symmetric, three-dimensionally expanding, finite source. The parameters of the model emission function are constrained by fits to neutron and proton momentum distributions and correlation functions in intermediate energy heavy-ion collisions. The temperature gradient… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 28 publications
0
43
0
Order By: Relevance
“…The method based on self-similar flow initially introduced to find solutions for non-relativistic cases known as Buda-Lund approach [170,[425][426][427][428][429][430][431][432][433][434] has shown to be very powerful in studying the flow dynamics of non-relativistic hydrodynamics. Recently this approach was extended to include (rigid) rotation, and explicit solutions with rotation were found [435,436].…”
Section: Known Analytic Solutionsmentioning
confidence: 99%
“…The method based on self-similar flow initially introduced to find solutions for non-relativistic cases known as Buda-Lund approach [170,[425][426][427][428][429][430][431][432][433][434] has shown to be very powerful in studying the flow dynamics of non-relativistic hydrodynamics. Recently this approach was extended to include (rigid) rotation, and explicit solutions with rotation were found [435,436].…”
Section: Known Analytic Solutionsmentioning
confidence: 99%
“…[4] where it was shown that temperature gradient effects can indeed lead to effects similar to i) -iii). In ref.…”
Section: Application To Fopi Datamentioning
confidence: 99%
“…In ref. [4], the distributions of the hydrodynamical fields were parameterized, but the equations of hydrodynamics were not solved. It was shown that a temperature profile results in momentum dependence of the effective radius parameters of the proton-proton correlation functions and in a characteristic bending down of the proton spectra, observable as a deviation from the exponential spectrum [5].…”
Section: Application To Fopi Datamentioning
confidence: 99%
See 1 more Smart Citation
“…due to radiation). We hope that the results presented herewith may be utilized to access analytically the time-evolution of the hydrodynamically behaving strongly interacting matter as probed by non-relativistic heavy ion collisions [4,5]. The results are, however, rather general in nature and they can be applied to any physical phenomena where the non-relativistic hydrodynamical description is valid.…”
mentioning
confidence: 99%